Analysis of gender roles in agro-industrial workers' families - Hasyim, Fuad; Indriani, Yaktiworo; Sayekti, Wuryaningsih Dwi (Universitas Islam Negeri Ar-Raniry, 2022)
This study aimed to analyze the role division of husband and wife in dual earner families based on gender. Basically, gender roles can be defined as the social relationship between husband and wife and the social construction resulted from that relationship. The consequence is the roles division based on gender may vary between communities, but it can be analyzed by its types (patrilineal, matrilineal, and egalitarian). This research was conducted purposively in Seputih Mataram Sub-district of Central Lampung Regency of Lampung Province by survey method. The research samples were 85 dual earner families, in which husband and wife of the family work as laborers in agricultural or agro-industry companies. The results of this research indicated that the family of agro-industry workers belonged to the patrilineal type family. Patrilineality in the family could be based on the division of family gender roles. Gender roles in the domestic sphere was charged to wives and in the social sphere was charged to husbands. This happens because of the social construction process that has been going on from one generation to another. It could be proven, for example, by meeting invitations on social activities from the village office are often addressed to husbands. In the domestic area, the division of gender roles is based on the division of tasks based on gender appropriateness, for example the task of cooking is charged to the wife and the task of repairing the house is charged to the husband.